The possibilities of using the guidebook analysis method in research on the evolution of urban tourism space in Maghreb countries - Kalaska, Maciej (Turyzm/Tourism, 2018)
Research on the evolution of tourism space in Maghreb cities is hindered due to the limited availability and questionable credibility of the data. The guidebook analysis method was developed by S. Liszewski (1999) and it offers a way of analysing tourism space. The main objective of this research paper is to indicate the advantages and disadvantages of using this method to analyse changes in the urban tourism space of the Maghreb. This paper presents conclusions of the research conducted in six locations in the period 2012-2014.